An integrative approach to investigating longstanding organisational phenomena; opportunities for practice theorists and historians - Jarzabkowski, P; Bednarek, R; Kilminster, W; Spee, P (Taylor and Francis, 2021)
We add to the ongoing call for greater integration between organisational and history scholarship. Specifically, we contribute by identifying reciprocal opportunities for practice theorists and historians interested in the unfolding of socio-historic patterns over space and time. Through contrasting two studies of ‘relationship’ in the international reinsurance industry – one an ethnographic, practice-based study, the other an archival, historic analysis – we illuminate the differences between and also complementarities of the two approaches. Understanding such differences provides the foundation for a more reflexive construction of future research design. Using the insights gained by contrasting the two studies we show how a more integrative approach allows the extension of organisational constructs and theories.